2016
DOI: 10.1177/1087054716648775
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Effects of Parent Training for Preschool Children With or at Risk of ADHD: A Systematic Review and Meta-Analysis

Abstract: PT was partially supported as an efficacious intervention for preschool children with ADHD or ADHD symptoms with moderate ESs on parent-rated outcomes, but no significant results on independently assessed ADHD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 54 publications
2
74
0
9
Order By: Relevance
“…Fathers and mothers reported significant and large improvements of children's behaviours after BPT, both in intensity and number of problematic behaviours (effect sizes ranged from 0.51-0.87). Especially the father reports on child outcome are informative, as these reports are scarce (Rimestad et al, 2016). Although we did not include a control group in our study design, the significant improvements after BPT stand out from the non-significant changes during the waiting list period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fathers and mothers reported significant and large improvements of children's behaviours after BPT, both in intensity and number of problematic behaviours (effect sizes ranged from 0.51-0.87). Especially the father reports on child outcome are informative, as these reports are scarce (Rimestad et al, 2016). Although we did not include a control group in our study design, the significant improvements after BPT stand out from the non-significant changes during the waiting list period.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral parent training (BPT) is a first-line treatment for preschool children with disruptive behaviours (Charach, Carson, Fox, Ali, Beckett, & Lim, 2013;Comer, Chow, Chan, Cooper-Vince, & Wilson, 2013;LaForett, Murray, & Kollins, 2008;Mulqueen, Bartley, & Bloch, 2013), and its efficacy has been confirmed in meta-analyses (Charach et al, 2013;Comer et al, 2013;Mulqueen et al, 2013;Rimestad, Lambek, Zacher Christiansen, & Hougaard, 2016). BPT aims to decrease disruptive behaviour problems in children by enhancing parenting skills.…”
Section: Introductionmentioning
confidence: 99%
“…48 A recent systematic review and meta-analysis which assessed the effects of parent training for pre-school children with, or at risk of, ADHD showed a moderate effects size for reduced ADHD symptoms which was sustained at 3-12 month follow-up. 5 This review found no moderation effect for programme type.…”
Section: Discussionmentioning
confidence: 79%
“…It is estimated that 2% to 6% of pre-schoolers meet the criteria. 5 A worldwide review found an ADHD prevalence rate of 5.29% with a range from about 1.5% to 10%, with the variability attributed partly to differences in the two main internationally recognised guidelines for diagnosis -the International Classification of Diseases and the Diagnostic and Statistical Manual of Mental Disorders. 1 Gender differences have been found, with the ratio of males to females ranging from 2:1 to 10:1.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrate positive outcomes following parent-training programs in the preschool age group (Lange et al, 2018;Rimestad, Lambek, Zacher Christiansen, & Hougaard, 2016;Webster-Stratton, Reid, & Beauchaine, 2011), but evidence for parent-training interventions in the management of ADHD in preadolescents is variable (Kleve et al, 2011;MTA Cooperative Group, 1999;Sayal et al, 2016;Stattin, Enebrink, Özdemir, & Giannotta, 2015;Zwi, Jones, Thorgaard, York, & Dennis, 2011). Several studies demonstrate positive outcomes following parent-training programs in the preschool age group (Lange et al, 2018;Rimestad, Lambek, Zacher Christiansen, & Hougaard, 2016;Webster-Stratton, Reid, & Beauchaine, 2011), but evidence for parent-training interventions in the management of ADHD in preadolescents is variable (Kleve et al, 2011;MTA Cooperative Group, 1999;Sayal et al, 2016;Stattin, Enebrink, Özdemir, & Giannotta, 2015;Zwi, Jones, Thorgaard, York, & Dennis, 2011).…”
Section: Parent-training Programsmentioning
confidence: 99%